Direct Detection of Circulating Tumor Cells in Whole Blood Using Time‐Resolved Luminescent Lanthanide Nanoprobes. Issue 35 (25th July 2019) - Guo, Hanhan; Song, Xiaorong; Lei, Wen; He, Cheng; You, Wenwu; Lin, Qingzhong; Zhou, Shanyong; Chen, Xueyuan; Chen, Zhuo
Abstract: The detection of circulating tumor cells (CTCs) is crucial to early cancer diagnosis and the evaluation of cancer metastasis. However, it remains challenging due to the scarcity of CTCs in the blood. Herein, we report an ultrasensitive platform for the direct detection of CTCs using luminescent lanthanide nanoprobes. These were designed to recognize the epithelial cell adhesion molecules on cancer cells, allowing signal amplification through dissolution‐enhanced time‐resolved photoluminescence (TRPL) and the elimination of short‐lived autofluorescence interference. This enabled the direct detection of blood breast‐cancer cells with a limit of detection down to 1 cell/well of a 96‐well plate. Moreover, blood CTCs (≥10 cells mL −1 ) can be detected in cancer patients with a detection rate of 93.9 % (14/15 patients). We envision that this ultrasensitive detection platform with excellent practicality may provide an effective strategy for early cancer diagnosis and prognosis evaluation. Abstract : The direct detection of circulating tumor cells (CTCs) was performed in whole blood using time‐resolved luminescent lanthanide nanoprobes. This strategy exhibited a detection limit down to 1 cell/well of a 96‐well plate (200 μL) without the need for enrichment steps, allowing cancer diagnosis with a detection rate of 93.9 %. This approach demonstrates the great promise of CTC detection in cancer diagnosis.